Vortices and propulsion - Arellano, R. (coachesinfo.com, 1999)
A review of the general theory of swimming propulsion is presented relating this with knowledge about vortices in steady and unsteady flow conditions. Three methods of flow visualisation have been used in the experiments: a) injecting air bubbles close to big toe during undulatory underwater swimming and breaststroke kick; b) putting reflective particles in water to see hand short movements and; c) injection of air bubbles in the swimming pool creating a 'bubble wall', making it possible for the swimmer to cross and to swim along it. The results of the experiments showed that: a) vortices are generated during different phases of the stroke and during the downward kick in undulatory swimming, flutter kick and breaststroke kick; b) when the hand suddenly changes the direction of its movement the starting vortex is detached from the hand and; c) the size and movement characteristics of the vortex seem related to propulsion obtained by the hand and foot movements. (Introduction: The Basics of Swimming Propulsion, What is a Vortex? Flow Visualisation Techniques)